2020
DOI: 10.1177/0040517520948904
|View full text |Cite
|
Sign up to set email alerts
|

Structure optimization of an ultrahigh frequency radio frequency identification tag thread based on the normal mode helix dipole antenna

Abstract: This paper describes the design of a novel ultrahigh frequency radio frequency identification (UHF RFID) tag thread that mainly consisted of the common yarn and the normal mode helix dipole antenna. The linear dipole antenna for the UHF RFID tag thread was too long to miniaturize the tag. In order to maximize the read performance and miniaturize the size of the tag, the basic antenna structure parameters, such as the helical pitch and single arm length, were optimized by analyzing the radiation parameter S11 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(18 reference statements)
0
4
0
Order By: Relevance
“…For the NMHDA with the helical radius of 0.55 mm and the single arm length of 63.0 mm, when the helical pitch increased from 1.0 mm to 2.0 mm, the resonant frequency increased more than 150 MHz. 10 Obviously, the change of resonant frequency in the above cases were greater than the Chinese UHF RFID band (920–925 MHz). These results demonstrates that the structure uniformity from manufacturing process has a significant impact on the resonant frequency of UHF RFID tag thread with NMHDA.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For the NMHDA with the helical radius of 0.55 mm and the single arm length of 63.0 mm, when the helical pitch increased from 1.0 mm to 2.0 mm, the resonant frequency increased more than 150 MHz. 10 Obviously, the change of resonant frequency in the above cases were greater than the Chinese UHF RFID band (920–925 MHz). These results demonstrates that the structure uniformity from manufacturing process has a significant impact on the resonant frequency of UHF RFID tag thread with NMHDA.…”
Section: Introductionmentioning
confidence: 90%
“…Helical pitch. According to the geometric size of the common UHF RFID tag thread with NMHDA, 10,11 the helical radius was set to 0.615 mm. The helical pitches were randomly generated by the normal distribution.…”
Section: Numerical Simulation and Analysis Methods Of Geometry Struct...mentioning
confidence: 99%
“…Firstly, the helical pitch and single arm length of NMHDAs were set as the extreme values of their respective ranges and are listed in Table 1. In addition, previous work 3 showed that an UHF RFID tag thread with a helical pitch of 1.0 mm, a single arm length of 43.0 mm, and a helical radius of 0.55 mm had good reading performance, and this case was also included in Table 1 to validate Equation (13).…”
Section: Validationmentioning
confidence: 99%
“…The geometry structure of the UHF RFID tag thread based on a helical dipole antenna is shown in Figure 1. According to previous work, 2,3 because A ≪ λ , the helix dipole antenna for the UHF RFID tag thread works as a normal mode helix dipole antenna (NMHDA), that is, the radiation pattern of the antenna is maximum in a plane normal to the axis of the helix. The NMHDA mainly works near the resonant frequency for great reading performance.…”
mentioning
confidence: 99%